AODV-Based Backup Routing Scheme in Mobile Ad Hoc Networks - Tsung-Chuan Huang; Sheng-Yu Huang; Lung Tang (2010 International Conference on Communications and Mobile Computing, 2010)
As effective routing is critical in mobile ad hoc networks (MANETs), the Ad hoc On-demand Distance Vector (AODV) has been extensively studied in recent years. Given that AODV requires a new route discovery procedure whenever a link breaks, such frequent route discoveries incur a high routing overhead and increase end-to-end delay. Therefore, by modifying the AODV protocol, this work presents a novel backup routing scheme capable of repairing disrupted links locally without activating a route re-discovery procedure. Additionally, backup paths are established based on 2-hop neighbor knowledge. These backup paths are geographically close to the primary path in order to provide efficient recovery from route failure and maintain an adequate routing length. Simulation results indicate that the proposed backup routing scheme obtains a lower average end-to-end delay and less routing overhead than those of the Ad hoc On-demand Multipath Distance Vector (AOMDV) and the conventional AODV.